2022
DOI: 10.1021/acs.orglett.2c00580
|View full text |Cite
|
Sign up to set email alerts
|

Rh(III)-Catalyzed Synthesis of Indazolo[2,3-a]quinolines: Vinylene Carbonate as C1 and C2 Building Blocks

Abstract: A rhodium-catalyzed cyclization of azobenzenes and vinylene carbonate via C−H bond activation to construct indazolo[2,3-a]quinolines has been developed. This protocol offers an efficient method for synthesis of the titled products in good yields with broad functional group tolerance. In this reaction, three C−C bonds and C−N bond are formed in one pot, and vinylene carbonate (VC) acts as C1 and C2 synthons as well as "vinylene transfer" agent and acylation reagent in the construction of targetfused heterocycle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 65 publications
0
10
0
1
Order By: Relevance
“…In this aspect, Cui and co-workers uncovered Rh(III)-catalyzed cyclization of azobenzenes with two VCs for the synthesis of indazolo[2,3-a] quinolines (Scheme 36). 85 The authors found that the rhoda- materials and biosensors. Regrettably, unsymmetric substrates proceeded with low chemoselectivity under the standard conditions (114c and 114d).…”
Section: Three-component Cyclization With Two Vcsmentioning
confidence: 99%
“…In this aspect, Cui and co-workers uncovered Rh(III)-catalyzed cyclization of azobenzenes with two VCs for the synthesis of indazolo[2,3-a] quinolines (Scheme 36). 85 The authors found that the rhoda- materials and biosensors. Regrettably, unsymmetric substrates proceeded with low chemoselectivity under the standard conditions (114c and 114d).…”
Section: Three-component Cyclization With Two Vcsmentioning
confidence: 99%
“…Inspired by previous studies 14 and our continuing effort toward the easy construction of heterocycles based on metal-catalysed C(sp 2 )–H bond functionalization, 15 we disclose herein an Rh( iii )-catalysed [4 + 2] annulation of easily available 3-aryl-1- H -indazoles with propargyl alcohols, affording the unprecedented 6-alkenylindazolo[3,2- a ]isoquinolines. This reaction exhibited excellent regioselectivity and functional group tolerance under mild reaction conditions (Scheme 1).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, our group developed rhodiumcatalyzed cyclization of azobenzenes with vinylene carbonate via C-H bond activation to construct non-substituted indazolo[2,3-a]quinolines (Scheme 1c). [9] The vinylene carbonate (VC) acts as C(1) and C(2) synthons as well as "vinylene transfer" and acylation reagent in this transformation. On the other hand, sulfoxonium ylides, as versatile synthetic precursor, have emerged in C-H functionalization [10] because of its safe and higher coordination affinity with the metal center, leading to easily convert carbonyl compounds and provide the possibility to construct complex molecules through tandem annulation in "one-pot" manner.…”
Section: Introductionmentioning
confidence: 99%